Visita domiciliária como componente do PSF: compreendendo as percepções dos usuários dos serviços no Município de Fortaleza(CE) - Albuquerque, Adriana Bezerra Brasil de (2006)
Although a public health practice since the early 20th century, home visits by health care teams from the newly implanted family health program have become increasingly popular over the past decade. The present study looks into users’ perceptions of home visits within the context of the family health program with respect to completeness and humanization of care. The study was explorative and qualitative. Based on hermeneutic phenomenology and within a critical-interpretive perspective, the study contrasts the phenomenon under investigation with its own materiality in search of transforming elements. To this end 21 interviews were carried out in depth with users receiving home visits by family health teams within the six administrative health districts of Fortaleza. The empirical evidence of the study consisted of taped and transcribed interviews. An analysis of the interviews revealed the existence of three core themes: 1) Health professional/user relationships, i.e. users’ perceptions of completeness and humanization of care during visits. This theme was divided into three items: perception of health professional/user relationships, humanization of care and the meaning of completeness; 2) Characterization of visits, with emphasis on priorities and operationalization. The theme was divided into two items: frequency/duration of visits and patient selection; and 3) User/health facility association, with focus on health facility management and integration with other services, divided into three items: health facility management, equity and integration of care. In conclusion, the study suggests that home visiting practices may be improved by enhancing the aspects of closeness, conversation and constant negotiation between professionals, users and the community.